Analysis of the Effect of Intercritical Annealing Combined with Repetitive Hammering on Low Carbon Steel - Septa Setiawan, Bagus
In the metal industry there is a big challenge for obtaining lightweight material but still has high mechanical properties so that high specific mechanical properties are obtained. One technique of metal engineering is to combine plastic deformation and heat treatment, commonly called thermomechanical treatment. This study was conducted to determine the effect of intercritical annealing combined with plastic deformation using a repetitive hammer on carbon steel with 0.08% and 0.147% wt C. Intercritical annealing is carried out at a temperature of 800 ° C with a holding time of 10 minutes. Plastic deformation is given by pounding specimens as much as 20, 60 and 100 times using a load of 5 kg dropped from a height of 1 meter. Then observed changes in microstructure and hardness value of the material. The results showed that the intercritical annealing process in both samples of steels produced fine pearlite and bainite phases and had a ferrite matrix. However, the process does not provide a significant increase in hardness. A more significant increase in hardness is produced when combined with plastic deformation due to the strain hardening effect.